Target meta-awareness is a necessary condition for physiological responses to masked emotional faces: evidence from combined skin conductance and heart rate assessment - Myron, Tsikandilakis; Chapman, Peter; Peirce, Jonathan (Elsevier, 2018)
Much heated debate surrounds the extent to which we can process emotional stimuli without awareness. In particular the extent to which masked emotional faces can elicit changes in physiology measurements, such as heart rate and skin conductance responses, has produced controversial findings. In the present study, we aimed to determine whether briefly presented faces can elicit physiological changes and, specifically, whether this is due to unconscious processing. We measured and adjusted for individual differences in the detection threshold using both receiver operating characteristics and hit rates. For this we also used a strict Bayesian assessment of participant thresholds. We then measured physiological responses to threshold adjusted emotional faces and for hits, misses and post-binary subdivisions of target meta-awareness. Our findings based on receiver operating characteristics revealed that, when faces were successfully masked there were no significant physiological differences in response to stimuli with different emotional connotations. In contrast, when targets were masked based on hit rates we did find physiological responses to masked emotional faces. With further analysis we found that this effect was specific to correct detection of angry and fearful faces and that increases in experienced arousal were associated with higher confidence ratings for correct detection of these stimuli. Collectively, our results do not support the notion of unconscious processing when using markers of physiological processes. Rather they suggest that target meta-awareness is a necessary condition for -- and possibly determined by -- physiological changes in response to masked emotional faces.